Germany: School-to-School Collaboration at the Interface of Bureaucracy and Autonomy - Liegmann, Anke; Bremm, Nina; Van Ackeren, Isabell; Breiwe, René; Endberg, Manuela; Rutter, Sabrina (School-to-School Collaboration: Learning Across International Contexts, 2022)
School networks are of increasing importance in the Germany. Despite not being formally anchored in the structure of the school system, school networks are promoted via a wide variety of programmes. These initiatives have varying aims such as the systemic promotion of school development and the identification of key factors for success. Some programmes even provide for accompanying research into the impact of networks on their success. Following the classification of the German school system according to the cohesion/regulation matrix by Chapman, and suggesting an emphasis on ‘egalitarian culture’, this chapter then focuses on the topic of school-to-school collaboration. Doing so, we shall define our understanding of school networks, present a typology of commonly found networks in Germany and provide systemic examples of some of the larger school networks. The review of the national state of research in this field including experience from two of our research and development projects shows desiderata especially concerning processes of school-to-school collaboration. The role of school leadership, which will be expanded upon further, has proven to be a driver of success in school networks.<br
Keywords: School networks; network initiators; school leadership; school development; transfer; school governance